Associations Between Sleep Duration and Sensory Impairments Among Older Adults in China - Rong, Hongguo; Wang, Xiao; Lai, Xiaozhen; Yu, Weijie; Fei, Yutong (Frontiers in Aging Neuroscience, 2022)
Objective: Little is known about the associations between sleep duration and sensory impairments in China. This study aims to explore the associations between sleep duration and single or dual sensory impairments (visual and/or hearing). Methods: This cross-sectional study used the data from 17 668 respondents were drawn from the 2018 survey of the China Health and Retirement Longitudinal Study (CHARLS), an ongoing national longitudinal study of Chinese adults aged 45 years and above. The duration of sleep per night was obtained from face-to-face interviews. The presence of sensory impairments was measured by self-reported visual and hearing functions. Multivariable generalized linear models (GLM) with binomial family and log link to assess the associations between sleep duration and sensory impairments. Results: Of the 17 668 respondents, 8396 (47.5%) were men. The mean (SD) age was 62.5 (10.0) years old. Respondents with short (≤4, 5hours per night) sleep duration had a significantly higher risk of visual, hearing and dual sensory impairments than those who slept for 7 hours per night after adjusting for covariates (P < 0.05). Meanwhile, respondents who slept for 6 hours per night had a higher risk of hearing impairment (P = 0.005). Further analysis suggested a U-shaped association between sleep duration and sensory impairments. When sleep duration fell below 8 hours, increased sleep duration was associated with a significantly lower risk of visual (OR, 0.93; 95%CI, 0.88-0.98; P = 0.006), hearing (OR, 0.89; 95%CI, 0.86-0.93; P < 0.001), and dual (OR, 0.90; 95%CI, 0.87-0.94; P < 0.001) impairments. When sleep duration exceeded 8 hours, the risk of visual (OR, 1.09; 95%CI, 1.00- 1.19; P = 0.048), hearing (OR, 1.04; 95%CI, 0.97-1.11; P = 0.269), and dual (OR, 1.07; 95%CI, 1.00-1.14; P = 0.044) impairments would increase facing prolonged sleep duration. Women and the elderly aged over 60 years old were more sensitive to short sleep duration and experienced a higher risk of sensory impairments. Conclusion: In this study, short sleep duration was associated with a higher risk of visual and hearing impairments. Future studies are needed to examine the mechanisms of the associations between sleep duration and sensory impairments.